Language and Politics: Languages of Borderland - Palacio Avendaño, Martha (Millcayac - Revista Digital de Ciencias Sociales, 2025)
This paper deals with the idea of borderlands proposed by Chicana feminist Gloria Anzaldúa in Borderlands/La frontera. The New Mestiza (1987). In contrast to the geopolitical notion of the border as a defensive space, G. Anzaldúa suggests that borderlands is a dwelling place. The paper focusses on the elements that explain why borderlands implies a framework of understanding the experience of living between two worlds, and it is a social and political condition that enables the process of the collective identity political formation of Chicanos and Chicano feminism. In sum, the text wants to show how Anzaldúa's idea of borderlands poses a framework for understanding intersectionality in the process to create a new political voice.